Fenton-like degradation of methylene blue using Mg/Fe and MnMg/Fe layered double hydroxides as reusable catalysts - Gonçalves, Rosembergue Gabriel Lima [UNESP] (2020)
In this work, the Layered Double Hydroxide (LDH) containing magnesium (Mg) and iron (Fe) was modified with Mn to investigate the effect of the addition from the structural and catalytic point of view. These materials were characterized by X-ray powder diffraction (XRD), scanning electron microscopy (SEM), N2 adsorption-desorption isotherms, X-ray photoelectron spectroscopy (XPS), thermogravimetric analyses, and evaluated as heterogeneous catalysts in Fenton-like reaction. The results showed that the Mn was incorporated in the LDH, promoting structural changes such as reduction of crystallographic parameters, decrease of crystallite size, and increase of surface area. The removal of methylene blue (MB) in aqueous solutions by LDH with and without Mn showed better results with increasing catalyst dosage, H2O2 volume, and temperature; and that under the best reaction conditions, the MnMgFe-LDH was the catalyst more efficient in removing MB, being reused for 5 reaction cycles with more than 80% removal.